THE RELATIONSHIP BETWEEN JOB SATISFACTION DIMENSIONS AND EMPLOYEE RETENTION - Nurshahirah Amira, Audi Ashraf (Universiti Malaysia Sarawak (UNIMAS), 2021)
The purpose of this research is to study the relationship between job satisfactions dimensions such as pay, job security, compensation and benefits and working conditions on employee retention. This study used the Statistical Package for the Social Sciences (SPSS) to analyze the job satisfaction and employee retention through the questionnaire. The need of this study is to provide evidence of employee retention in public sector in the current limitation of quantitative data of employee retention. Accordingly, this research will provide the data to prove that the employee retention perceived by the job satisfaction dimensions of pay, job security, compensation and benefits and working conditions. The data for this study was collected using questionnaire which use a simple random sampling techniques. Data for this study was analyzed using statistical method which is SPSS. The data analysis determined whether the job satisfaction dimensions of pay, job security, compensation and benefits and working conditions influence employee retention in organization. The method used in this research is T-test, Pearson’s Correlation and Multiple Regression. The results shows the job satisfaction dimension of pay is the most dominant among the four dimensions. Thus, the questionnaire was distributed to one organization in Sarawak. The knowledge gained from this research can be applies in the organization for improvement